A NOVEL IRON SULPHIDE MINERAL SWITCH AND ITS IMPLICATIONS FOR EARTH AND PLANETARY SCIENCE - Rickard D.; Butler I.B.; Oldroyd A. (My University, 2001)
We report that iron sulphide mineral products of different compositions and oxidation states are produced by the catalytic activities of aldehydic carbonyl groups. We show that the product of the oxidation of iron(II) monosulphide (FeS) by aqueous H2S at temperatures between 40 and 100°C under anoxic conditions is dependent on the presence of catalytic quantities of aldehydes. The products switch between the ferrimagnetic thiospinel, greigite (Fe3S4) and the iron disulphide, pyrite (FeS2). Compared with other mineral switches, the effect of this first observed switch in the iron sulphide system is quite dramatic. In the presence of aldehydic carbonyls, the Fe(II) in iron(II) monosulphide is oxidised, but the S(-II) is unaffected; in the absence of aldehydic carbonyls, the S(-II) in the iron(II) monosulphide is oxidised but the Fe(II) remains unchanged. The effectiveness of the aldehyde switch is such that it suggests that the presence of trace organics can determine the stoichiometry and oxidation state of the iron sulphide product. The results have general implications for the coupling of iron sulphides with prebiotic organic systems in the early development of life. They provide a potential new pathway for the development of biogenic greigite, with implications for the development of remanent magnetism in sediments and suggest possible constraints on the use of greigite as a biomarker in Earth and planetary sciences.
Keywords: IRON SULFIDES; GREIGITE; PYRITE; ORGANIC COMPOUNDS; CATALYSIS